The Impact of Online Learning during the Covid-19 Pandemic on Academic Outcomes for Newly-Struggling High School Students - Kristine Webster (Online Learning, 2024)
The Covid-19 pandemic caused worldwide closures of schools resulting in a sudden shift to online instruction for students.  For many students, this shift caused a decrease in academic performance. This study was conducted to explore whether particular demographic variables were associated with decreased academic outcomes for newly-struggling students as well as to determine if there was a relationship between these demographic variables and the frequency of D and F final course grades.  Student final course grades were collected from a Midwestern United States high school’s student information system.  The data were used to compare academic performance between the fall semester of 2019 during in-person learning and the fall semester of 2020 when the Covid-19 pandemic resulted in school closures and a shift to online learning.  Logistic regression analysis was used to answer each of the research questions. The findings from this study suggest that there was a significant relationship between low household income status and status as a newly-struggling student.  Additionally this study suggests a significant relationship between low household income status and an increased frequency of D and F final course grades between semesters when compared with sample group peers.  Conversely, while special education students did see an increase in frequency of D and F final course grades between semesters it was a significantly lower increase between semesters than their newly-struggling sample group peers.